Comment on ‘Musculoskeletal Ultrasound Assessment of the Clinical Efficacy of the Combination of Acupressure and “Three Methods of Neck Movement (TCM)” Therapy in the Treatment of Cervical Spondylosis: A Study Protocol for a Randomized Controlled Trial’ [Letter] - Lv S; Guo R (Journal of Pain Research)
Shibei Lv,1 Rubao Guo2 1The Third School of Clinical Medicine (School of Rehabilitation Medicine), Zhejiang Chinese Medical University, Hangzhou, Zhejiang, 310053, People’s Republic of China; 2Department of Tuina, The Third Affiliated Hospital of Zhejiang Chinese Medical University, Hangzhou, Zhejiang, 310005, People’s Republic of ChinaCorrespondence: Rubao Guo, Department of Tuina, The Third Affiliated Hospital of Zhejiang Chinese Medical University, Hangzhou, Zhejiang, 310005, People’s Republic of China, Email guorubao129@126.com